Parents’ Views on Family Resiliency in Sustainable Remote Schooling during the COVID-19 Outbreak in Finland - Teija Koskela; Kaisa Pihlainen; Satu Piispa-Hakala; Riitta Vornanen; Juha Hämäläinen (MDPI, 2022)
The closure of schools because of the COVID-19 pandemic created a challenge for families
and teachers in supporting children’s remote schooling. This study investigates parents’ perspectives
on their accommodation to the rapid change to remote schooling from the point of view of sustainable
education. The study was conducted at the beginning of the COVID-19 pandemic in spring 2020
via an online questionnaire for parents, to which 316 voluntary participants responded. Data were
analyzed using a theory-driven content analysis. According to the results, parents were worried about
the learning and wellbeing of their children as well as management of daily life and use of information
and communications technology (ICT). The results show the importance of schools and teachers as
well as networks in supporting family resilience during rapid changes. Families’ individual needs
should be acknowledged and met in a sustainable way to support children’s learning in changing
settings, including remote schooling.